Imprisoning communities how mass incarceration makes disadvantaged neighborhoods worse - Clear, Todd R. (Oxford : Oxford University Press, 2007)
A detailed and empirical exploration of the effects of mass incarceration in poor areas, 'Imprisoning Communities' demonstrates that, in high doses, incarceration contributes to the very social problems it is intended to solve.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Imprisonment -- Social aspects -- United States; Social problems -- United States; Urban poor -- United States; Criminal justice, Administration of -- United States; Community-based corrections -- United States